Characteristics of strokes associated with centrifugal flow left ventricular assist devices - Ovais Inamullah (Nature Portfolio, 2021)
Abstract Stroke is a devastating complication of left ventricular assist device (LVAD) therapy. Understanding the characteristics, risk factors and outcomes of strokes associated with the centrifugal flow LVADs is important to devise better strategies for management and prevention. This is a retrospective cohort study at a single US academic medical center. The cohort includes patients who received a first time Heartmate 3 (HM3) or Heartware (HVAD) LVAD between September 2009 through February 2018 and had a stroke while the LVAD was in place. Descriptive statistics were used when appropriate. A logistic regression analysis was used to determine predictors of poor outcome. Out of a total of 247 patients, 12.1% (N = 30, 24 HVAD and 6 HM3) had a stroke (63% ischemic) and 3 of these patients had pump thrombosis. Events per patient year (EPPY) were similar for HVAD and HM3 patients (0.3 ± 0.1). INR was subtherapeutic in 47.4% of ischemic stroke patients and supratherapeutic in 18.2% of hemorrhagic stroke patients. Concurrent infections were more common in the setting of hemorrhagic stroke than ischemic stroke (45.4% vs 5.3%, p = 0.008). Strokes were severe in most cases, with initial NIH stroke scale (NIHSS) higher in HM3 patients compared to HVAD patients (mean 24.6 vs 16) and associated with high in-patient mortality (21.1% of ischemic stroke vs. 88.8% of hemorrhagic stroke). Predictors of death within 30 days and disability at 90 days included creatinine at stroke onset, concurrent infection, hemorrhaghic stroke, and initial stroke severity (NIHSS). A score derived from these variables predicted with 100% certainty mortality at 30 days and mRS ≥ 4 at 90 days. For patients with centrifugal flow LVADs, ischemic strokes were more common but hemorrhagic strokes were associated with higher in-patient mortality and more frequently seen in the setting of concurrent infections. Infections, sub or supratherapeutic INR range, and comorbid cardiovascular risk factors may all be contributing to the stroke burden. These findings may inform future strategies for stroke prevention in this population.